Parametric influence of magneto elasticity, initial stresses, porosity and thickness ratio on the phase and attenuation traits of SH-waves. (July 2022) - Kumari, Chandani; Kundu, Santimoy; Maity, Manisha; Gupta, Shishir
The present study is devoted to investigate the traversal of shear horizontal wave (SH-waves) in an initial-stressed fluid saturated porous stratum bounded between an initial-stressed magneto-elastic upper stratum and an initial-stressed elastic substrate. We have obtained the exact solution of the governing equations and explained in detail for various effective parameters. The displacement relation is developed with the help of Maxwell's fundamental equations and Maxwell's tensor. The impact of diverse parameters such as initial stress, porosity, magneto-elasticity, thickness ratio of attenuation coefficient and phase velocity of SH-wave has been discussed extensively by means of graphical depictions. Results indicate that such parameters possess a great positive impact on attenuation coefficient. This model contains a huge potential to deal with many commercial and industrial applications in Geo-technical, earthquake engineering and Geophysics.